Counter-ideological forces of "Mr Gate" in online Journalism in Malaysia: A study of MalaysiaKini and The Malaysian Insider - Mohd Faizal Kasmani; Sabran, R; Othman, SS; Ramle, NA (E D P Sciences, 2024)
Indexed by WOS